2004
DOI: 10.1002/elps.200406052
|View full text |Cite
|
Sign up to set email alerts
|

Ultrashort partial‐filling technique in capillary electrophoresis for infinite resolution of tramadol enantiomers and its metabolites with highly sulfated cyclodextrins

Abstract: The possibility to enhance resolution to infinite value in chiral capillary electrophoresis is attained as soon as the apparent mobility of one enantiomer becomes opposite to the other. This could be achieved on the basis of the carrier ability of multiple charged chiral selectors such as highly sulfated cyclodextrin (HS-CD). With tramadol and its phase I metabolites selected as model compounds, the HS-gamma-CD was found to be the most appropriate chiral selector. The CD concentration was determined where one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 57 publications
2
41
0
Order By: Relevance
“…Previous works demonstrated that the separation zone length containing the CD could be decreased. However, compared to the chiral selector concentration and gas nebulization pressure, the separation zone length (i.e., filled capillary percentage) was the less critical parameter to adjust [64,66,67]. After introducing the chiral BGE zone (ca.…”
Section: Stereoselective Analysismentioning
confidence: 99%
“…Previous works demonstrated that the separation zone length containing the CD could be decreased. However, compared to the chiral selector concentration and gas nebulization pressure, the separation zone length (i.e., filled capillary percentage) was the less critical parameter to adjust [64,66,67]. After introducing the chiral BGE zone (ca.…”
Section: Stereoselective Analysismentioning
confidence: 99%
“…For these compounds, only the second enantiomer reached the cathodic detection side. This phenomenon called infinite resolution was already described and investigated elsewhere [50,51].…”
Section: Low Hs-ª-cd Concentrationmentioning
confidence: 92%
“…As LC remains the most widely used technique in the pharmaceutical industry, the discussion will be limited to this approach even if capillary electrophoresis presents some obvious advantages for fast enantioseparations. [9][10][11][12] In 2003, monolithic supports were coated with a chiral selector to perform fast enantioseparations. This material presents some interesting characteristics related to its bimodal structure of macropores and mesopores.…”
Section: 2mentioning
confidence: 99%